Pengelolaan Sarana Pembelajaran di Kelas dalam Mendukung Mutu Pendidikan di SD Negeri 18 Palembang - Afriantoni; Savira Aulia; Syifa Al Fadhilah; Sindi Andaresta; Nando Agung Pratama (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the management of classroom learning facilities in supporting the quality of education at SD Negeri 18 Palembang. The management of learning facilities is one of the important factors in supporting the smooth teaching and learning process at school. Well-managed learning facilities can help teachers deliver learning materials more effectively and improve students’ understanding of the subjects being taught. Therefore, the management of learning facilities needs to be carried out systematically in order to contribute to improving the quality of education. The problem in this study is how the management of classroom learning facilities supports the quality of education at SD Negeri 18 Palembang. This study used a qualitative approach with a descriptive method. Data collection techniques were carried out through observations and interviews with the principal and teachers at SD Negeri 18 Palembang. The data obtained were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the management of learning facilities at SD Negeri 18 Palembang includes planning, utilization, and maintenance of learning facilities. Planning was carried out through coordination between the principal and teachers to determine the required learning facilities. The utilization of learning facilities was carried out by teachers in classroom learning activities to assist in delivering learning materials to students. Meanwhile, the maintenance of learning facilities was conducted routinely so that the available facilities remained in good condition and could be used optimally.